2018
DOI: 10.1021/acs.chemrestox.8b00055
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nine Cancer-Associated Variants in Human DNA Polymerase κ

Abstract: Specialized DNA damage-bypass Y-family DNA polymerases contribute to cancer prevention by providing cellular tolerance to DNA damage that can lead to mutations and contribute to cancer progression by increasing genomic instability. Y-family polymerases can also bypass DNA adducts caused by chemotherapy agents. One of the four human Y-family DNA polymerases, DNA polymerase (pol) κ, has been shown to be specific for bypass of minor groove adducts and inhibited by major groove adducts. In addition, mutations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 56 publications
2
26
1
Order By: Relevance
“…When incorporation starts from a mismatch base pair (dT:dG or dT: N 2 ffdG), WT pol κ was able to incorporate the correct next base dA, which has been observed previously. , Likewise, other pol κ SNP variants T102A, H142Y, Y221C, N330D, N338S, and L383F were able to do so in the presence of undamaged DNA, some of them more robustly than WT pol κ (Figure A). In the presence of N 2 ffdG, pol κ SNP variants T102A, H142Y, R175Q, E210K, Y221C, N330D, N338S, K353T, and L383F were able to incorporate the correct dA base (Figure B).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…When incorporation starts from a mismatch base pair (dT:dG or dT: N 2 ffdG), WT pol κ was able to incorporate the correct next base dA, which has been observed previously. , Likewise, other pol κ SNP variants T102A, H142Y, Y221C, N330D, N338S, and L383F were able to do so in the presence of undamaged DNA, some of them more robustly than WT pol κ (Figure A). In the presence of N 2 ffdG, pol κ SNP variants T102A, H142Y, R175Q, E210K, Y221C, N330D, N338S, K353T, and L383F were able to incorporate the correct dA base (Figure B).…”
Section: Resultssupporting
confidence: 76%
“…A few SNPs of pol κ were found to be associated with breast cancer risk . Some missense mutations of pol κ have also been found in nonsmall cell lung cancer patients and in prostate, melanoma, lung, and large intestine cancers. , SNPs can affect protein function by either increasing or decreasing protein activity . Mutations that decrease the activity of DNA pol κ on damaged DNA could make cells more sensitive to DNA damaging agents like chemotherapeutics, while mutations that show increased activity of DNA pol κ could play a role in resistance to DNA damaging chemotherapy. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…54 The nucleotide excision repair pathway (NER) is one of the most important repairing mechanisms; polymorphisms harbored for genes in this pathway, such as ERCC1 , ERCC2 , ERCC3 , ERCC4 , ERCC5 , RAD23B , XPA , XPC, and XPE , affected the survival of Chinese patients receiving chemotherapy as treatment for esophageal cancer, 55 therefore, showing potential as prognostic biomarkers. By studying one-nucleotide changes in the translesion synthesis DNA polymerases from the Y family associated with breast cancer, Anctzak et al 56 found that these polymerases showed different activities in the presence of damaged DNA, which can inhibit protein expression or lead to the expression of dysfunctional proteins; thus, these polymorphisms can be exploited as potential biomarkers. In prostate cancer, polymorphisms in the repair genes XRCC1 , ERCC2 , ERCC1 , LIG4, and TP53 have been related with clinical variables such as tumor size and Gleason score, demonstrating that these polymorphisms could be potential prognostic biomarkers.…”
Section: Strategies For the Search Of New Biomarkersmentioning
confidence: 99%
“…This approach involves the search of single nucleotide polymorphisms (SNPs) resulting in missense mutations that are associated with a specific phenotype on a particular gene or genes, followed by atomistic simulations to characterize the impact of the mutation (2,3). We have previously employed this approach to uncover and characterize various cancerassociated mutations (2,4,5), including the prediction and experimental confirmation of a rescue mutation for a lung-cancer associated mutation on APOBEC3H (6). Although there are successful examples for the prediction of rescue mutations, a systematic method to discover these variants would be beneficial.…”
Section: Introductionmentioning
confidence: 99%